ANALISIS SEMIOTIKA POSTER FILM DILAN 1990 - Munawarah, Pyo Apriliana; Tomi, Muhammad (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This research examines how a sign works so that it impresses a meaning on the object of the Dilan 1990 movie poster. Posters are a tool for publication media or communication media which is a work of graphic art consisting of a combination of image and writing compositions on large or small paper. and has a very vital function in the marketing of film works. Dilan 1990 is an Indonesian drama genre film produced by Falcon Pictures and Max Pictures fronted by Fajar Bustomi as director and Pidi Baiq as director and story writer Dilan. The data were obtained through a literature review process and then dissected using Saussure's semiotic theory, supported by Darmaprawira's color theory, and Horby's poster theory. The results of the study show that the use of illustrations of the two main characters with the properties of an old motorbike, the title headline, and the subheadline that contains information, in general, can describe the story that will be shown in the film.